Analisa Rantai Pasok (Supply Chain) Bahan Baku pada Industri Kuliner Bebek dan Ayam Goreng (Studi Kasus : Depot Bebek dan Ayam Goreng Pak Qomar) - Zaidi, Abdul Hamid; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The aim of the research is to determine the flow of the duck supply chain which includes product flow, financial flow and information flow from duck breeders to the restaurant "Pak Qomar Duck and Fried Chicken Depot", to find out whether or not the supply chain is efficient and effective. happens from the breeder to the restaurant, and to find out the added value of the breeder, supplier, and the "Bebek Pak Qomar" restaurant. The results of this research are that there are 2 links that play an active role in the duck meat supply chain to the final consumer: (a) duck breeders and (b) duck suppliers. There are only two types of product flow in the duck meat supply chain at the "Bebek Pak Qomar" restaurant, namely the product flow in the form of live ducks originating from the farmer to supplier 2/3 and from supplier 2/3 to supplier 1, and to "Bebek Pak Qomar" restaurant for processing. The flow of information in the duck meat supply chain at the "Bebek Pak Qomar" restaurant is divided into two types of flow, namely the horizontal flow of information that occurs between fellow duck breeders and suppliers and suppliers and restaurant managers and the vertical flow of information that occurs at each eye. chain involved in the duck meat supply chain at the "Pak Qomar" restaurant. Financial flows in the duck meat supply chain at the "Bebek Pak Qomar" restaurant occur in 1 type of flow with the payment transaction system used during the distribution process greatly influencing the performance of each link in the chain. Measuring the amount of added value obtained using the added value calculation method xi and using BEP (Break Even Point) at the duck farmer level. The conclusion obtained from this research is the supply chain flow which includes the flow of products containing live ducks which are sent by breeders to suppliers and then to retail traders to be processed into processed duck meat at the "Bebek Pak Qomar" restaurant and served to final consumer.